Prevalence and predicting factors of increased arterial stiffness in autosomal dominant polycystic kidney disease - Nada Sellami; Rania Kheder-El Fekih; Hela Jebali; Ikram Mami; Wided Smaoui; Fethi Ben Hmida; Mohamed Karim Zouaghi; Lilia Ben Fatma; Lamia Rais (Saudi Journal of Kidney Diseases and Transplantation, 2021)
Carotid-femoral pulse wave velocity (cf-PWV) is the noninvasive gold standard technique for measuring aortic stiffness. Autosomal dominant polycystic kidney disease (ADPKD) is the most common genetic renal disease in adults. It is associated with a high risk of cardiovascular complications. We aimed to assess the prevalence of increased arterial stiffness and its predicting factors in a population of ADPKD patients. Sixty-two patients with ADPKD underwent noninvasive measurement of cf-PWV using a COMPLIOR Analyse device. Recruitment period was 17 months and we used the cut-off of 10 m/s to define a high cf-PWV. Mean age was 51 ± 12.7 years. Gender ratio male/female was 0.63. Smoking, hypertension (HTN), and dyslipidemia were reported in 14%, 66%, and 27% of the cases, respectively. Mean glomerular filtration rate (GFR) was 47.7 ± 44 mL/min/1.73 m2. Among our patients, 39% had chronic kidney disease stages 1 or 2 and 45% stage 5 (40% stage 5D). Mean cf-PWV was 9 ± 2.4 m/s, and 31% of the patients had a high cf-PWV. In univariate analysis of all our patients, cf- PWV correlated with age (r = 0.565; P <10-3), GFR (r = -0.268;P = 0.035), C-reactive protein (r = 0.447; P = 0.007), peripheral systolic arterial pressure (r = 0.309; P = 0.015), and peripheral pulse pressure (r = 0.335; P = 0.008). Patients with high cf-PWV were on average nine years older than the others. Patients with HTN were 3.84 times more likely to have high cf-PWV (P = 0.046). cf-PWV did not seem to be lower with any antihypertensive treatment. A level of C-reactive protein higher than 10 mg/L was the only independent predicting factor of a high cf-PWV in multivariate analysis (P = 0.043). Our study confirmed the relationship between cf-PWV and age, renal failure, and HTN in patients with ADPKD. It also emphasized the close relationship between systemic inflammation and arterial stiffness in this nephropathy.